KESEHATAN MENTAL DI KALANGAN PELAJAR SEKOLAH MENENGAH DI KOTA MEDAN: LONGITUDINAL TENTANG GAYA HIDUP DAN KESEHATAN - LESMANA SYAHRIR (JURNAL ILMIAH MAKSITEK, 2023)
Medan is one of the cities that prioritizes education is one of the benchmarks of improving the quality and capacity of human resources. During 2022, the number of secondary school students reached 229,945 people, of which the number of students who experienced mental disorders was around 5,560 people. This situation is not only caused by the family environment, but also due to a free lifestyle, where this free lifestyle they students already know the name of liquor and narcotics, and eat food that is not in accordance with what is required by the health office in Medan City. This study used descriptive longitudinal analytical method. The population of this study amounted to 29,100 people who experienced reproductive health problems, where reproductive health problems would cause sexual diseases. The population of this study amounted to 5,560 high school students in Medan City who experienced mental disorders, where the sample taken amounted to 68 high school students in Medan City who experienced mental disorders. The results stated that the number of high school students who experience many mental disorders are high school students in East Medan District who are in the age range of 15-19 years, where these mental disorders are mostly due to using risky things, such as drinking and narcotics.